2012
DOI: 10.1002/adfm.201201176
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Specific Capacitances for Supercapacitors Achieved by Nickel Cobaltite/Carbon Aerogel Composites

Abstract: Nickel cobaltite, a low cost and an environmentally friendly supercapacitive material, is deposited as a thin nanostructure of 3–5 nm nanocrystals into carbon aerogels, a mesoporous host template of high specific surface areas and high electric conductivities, with a two‐step wet chemistry process. This nickel cobaltite/carbon aerogel composite shows ultrahigh specific capacitances of around 1700 F g−1 at a scan rate of 25 mV s−1 within a potential window of −0.05 to 0.5 V in 1 M NaOH solutions. The composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
1
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(108 citation statements)
references
References 25 publications
0
101
1
5
Order By: Relevance
“…6a) conducted in a potential window between À0.15 and 0.35 V are 1273.10, 1211.25, 1178 F g À1 at 0.5, 1, 2 A g À1 , higher than those achieved by NiCo 2 O 4 shown in Fig. S2a fabricated with the same coprecipitation method, corresponding to the following equation: [39] where Cm refers to the specific capacitance, I is the current, m denotes the loading mass, Dt represents the discharge time, DU is potential window. In the magnified inset, the NCG-10 still remains high capacitance of 772.5 and 687 F g À1 at large current densities of 5 and 10 A g À1 .…”
Section: Electrochemical Characterization Of the Positive Electrode Nmentioning
confidence: 79%
“…6a) conducted in a potential window between À0.15 and 0.35 V are 1273.10, 1211.25, 1178 F g À1 at 0.5, 1, 2 A g À1 , higher than those achieved by NiCo 2 O 4 shown in Fig. S2a fabricated with the same coprecipitation method, corresponding to the following equation: [39] where Cm refers to the specific capacitance, I is the current, m denotes the loading mass, Dt represents the discharge time, DU is potential window. In the magnified inset, the NCG-10 still remains high capacitance of 772.5 and 687 F g À1 at large current densities of 5 and 10 A g À1 .…”
Section: Electrochemical Characterization Of the Positive Electrode Nmentioning
confidence: 79%
“…19d) Carbon aerogels (CA) are also a superior candidate for highly conductive porous matrix, which own a 3D well-connected through-pore structure. [161][162][163][164][165][166][167] These hierarchical carbon aerogels are always obtained from pyrolysis of polymer materials. As an example, Gutierrez et al 168 recently reported 3D carbon aerogels with hierarchical pores from PPO-PEO-PPO block copolymer.…”
Section: Other Carbon Materialsmentioning
confidence: 99%
“…The morphology and microstructure of the samples were studied using SEM; the results are shown in pores; it has high porosity in the range of 80-90%, stable mesopores with sizes ranging from 2-50 nm, and a large specific surface area [27][28][29][30][31][32]. Two different approaches have been adopted to improve the CO 2 adsorption capacities of porous carbons.…”
Section: Sem Analysesmentioning
confidence: 99%